Semi-Active Scissors-Seat Suspension With Magneto-Rheological Damper - Hongtao Zhu (Frontiers in Materials, 2020)
A cab seat suspension with a magneto-rheological (MR) fluid damper is introduced in this paper. A unified-format model for the MR damper is proposed to describe the dynamic characteristics of the MR damper. Also, a simple force-inverse model and a viscous damping tracking model are used for the coil current solution. A digital integrator and an extended Kalman filter are respectively adopted to obtain the vibration velocity of the chair frame and the relative motion velocity of the MR damper piston. A new skyhook control base with viscous damping tracking is applied to the semi-active seat suspension. In the simulation, compared with passive seat suspension under different displacement excitation (2, 4, 6, 8 Hz-sine, and random), the acceleration root mean square of the seat suspension with the MR damper is reduced by 52.2%, 32.2%, 41.3%, 50.8%, and 34.6%, respectively. In the experiment, the acceleration root mean square is reduced by 11.2%, 41.2%, 45.8%, and 31.5%, respectively under different displacement excitation (2, 4, 6, and 8 Hz-sine).